THE SOCIAL FUNCTIONS OF LAW (CIPEEX, 2025)
The social functions of law are analyzed in this study through a multidisciplinary approach. The objective of the research is to investigate how law plays different roles in society. Using qualitative methods, several relevant jurisprudences and legal theories were examined.  These functions are analyzed through a case study, which examines the impact of laws and regulations on people’s daily lives and social relations. Law plays a crucial role in structuring life in society, acting as a set of norms that regulate human behavior and interpersonal relationships. These standards not only establish rules of conduct, but also reflect and shape the values and expectations of a community. The results reveal that the social functions of law include not only the regulation of behaviors, but also the promotion of social justice, the protection of human rights and the guarantee of public order. But it is a fact that law influences and shapes social interactions and power relations according to its legal system, playing in society justice, order and general well-being. It is concluded that, in order for the social functions of law to be fully realized, it is necessary an efficient, accessible legal system that is in tune with the values and needs of society. In addition, the law acts as a mechanism for the protection of individual rights, ensuring that all persons are treated equally before the law and have their fundamental rights respected. This includes civil, political, social, and economic rights, such as the right to freedom of expression, the right to privacy, the right to health, and the right to decent work. This study emphasizes the importance of a multidisciplinary approach to understand the role of law in the construction and maintenance of a fair and democratic society. It is concluded that law is a fundamental instrument for social cohesion and the proper functioning of institutions. Understanding these social functions is crucial for the development and construction of a more just, democratic and inclusive society for all its members.
Keywords: sociology; law; social function